2006
DOI: 10.1111/j.1365-2702.2006.01405.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse discharge planning in the emergency department: a Toowoomba, Australia, study

Abstract: Aim. This study aimed to ascertain whether a model of risk screening carried out by an experienced community nurse was effective in decreasing re-presentations and readmissions and the length of stay of older people presenting to an Australian emergency department. Objectives. The objectives of the study were to (i) identify all older people who presented to the emergency department of an Australian regional hospital; (ii) identify the proportion of representations and readmissions within this cohort of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(76 citation statements)
references
References 12 publications
1
75
0
Order By: Relevance
“…Although the literature review presented beneficial outcomes in providing intensive CM at somatic hospital based ED, the authors concluded that there was a need for further studies covering how best to take care of frequent visitors to ED. This is a conclusion which is supported by other researchers [8,[19][20][21]. In Sweden and, to our knowledge, no intervention study covering models for reducing costs and frequent visits at ED has been published.…”
Section: Introductionsupporting
confidence: 79%
“…Although the literature review presented beneficial outcomes in providing intensive CM at somatic hospital based ED, the authors concluded that there was a need for further studies covering how best to take care of frequent visitors to ED. This is a conclusion which is supported by other researchers [8,[19][20][21]. In Sweden and, to our knowledge, no intervention study covering models for reducing costs and frequent visits at ED has been published.…”
Section: Introductionsupporting
confidence: 79%
“…Of them, only five studies demonstrated statistical significance in lowering ED use or ED length of stay (LOS) 27 31 32 36 37. None of them used RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Although the findings did raise issues in these areas, it is not clear why these were selected as conclusions of the review. There has been some work previously undertaken around consumer perceptions of practice nurse roles in the international context which may have provided more insight in this area 57…”
Section: Methodological Shortcomingsmentioning
confidence: 99%